PENERAPAN MODEL PEMBELAJARAN KOPERATIF MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA SDN SRONDOL KULON 02 TAHUN 2023 - Priscila Puspitasari; Nursiwi Nugraheni; Diana Apriliya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to evaluate and improve the learning outcomes of class V students in Indonesian language subjects at SDN Srondol Kulon 02 in 2023 through the application of the Make a Match cooperative learning model. The research method used is classroom action research (PTK) using a quantitative approach. The research subjects involved 28 VC class students at SDN Srondol Kulon 02. Data was collected through learning results tests, interviews and observations during two learning cycles. In cycle 1, the application of the Make a Match cooperative learning model provided student learning outcomes with a completion percentage for 16 students of 57%, in the good category. In this cycle, the main focus is understanding student responses to the learning model and identifying areas of improvement. The second cycle involves adjustments based on the results of the first cycle evaluation. The research results showed that with increased strategies and adaptations in the second cycle, there was a significant increase in student learning outcomes. At the end of cycle 2, the percentage of complete learning outcomes for 27 students reached 96%, in the very good category. Apart from increasing learning outcomes, it was also observed that increased student participation and collaboration during the learning process, had a positive impact on the development of learning models in the school environment. These findings provide a positive contribution in the context of using the Make a Match cooperative learning model. The implications of this research are: (1) Schools are advised to be more intensive in guiding teachers so that they adopt various learning models, including the make a match cooperative learning model. This aims to create a learning atmosphere that is not only active, but also interesting for students, with a focus on achieving learning goals optimally. (2) Teachers can utilize the make a match cooperative learning model as a variation in teaching, not only as a choice of learning model, but also as a tool to improve student learning outcomes. (3) For future researchers, it is recommended to prepare a more in-depth study regarding the application of the make a match cooperative learning model